Efektivitas Supervisi Akademik Pengawas PAI dalam Membina Guru Agama SMP dan SMA di Kecamatan Ipuh Kabupaten Mukomuko - Nasrul Hendri (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
This study aims to determine the effectiveness of Islamic education supervisors in fostering junior high school and senior high school religion subject teachers, including academic supervision on (1) planning, (2) implementation, (3) follow-up, (4) blocking and inhibiting factors. This research used an evaluative research approach. Respondents in this study amounted to 9 people, consisting of 2 supervisors and 7 Islamic teachers. Participants in this study consist of 1 Islamic education supervisor for junior high school, 1 Islamic education supervisor for senior high school, 5 Islamic education teachers in junior high school, and 2 Islamic education teachers in senior high school. Data were collected using the method of observation, interviews and documentation. The results of data analysis showed that the level of effectiveness of Islamic education supervisors in fostering Islamic educators in junior and senior high school has a score of 67.46%. It means less effective because supervisors do not master academic supervision techniques, rarely receive supervisory training, and take a long trip to teach between schools.